Striving for balance: A review of female dermatologists' perspective on managing a dual-career household, - Jaclyn Rosenthal, BSN; Karolyn A. Wanat, MD; Sara Samimi, MD (Wolters Kluwer, 2020)
As the gender gap in medicine continues to close, female dermatologists are striving to balance the competing demands of career ambitions and family responsibilities. Despite gaining a new sense of autonomy and personal fulfillment, working women report feelings of guilt, frustration, and exhaustion as they struggle to be a good doctor, partner, mother, family member, and friend. The presence of children in the household and the asymmetrical division of labor have been reported as main stressors for women in dual-career families. Finding time for self-care and maintaining a robust support system are effective strategies to mitigate these challenges.In this study, we performed a literature review to evaluate the internal and external pressures among working women in dual-career families. In addition, we provide the personal commentary of Sara Samimi and Karolyn A. Wanat, two female dermatologists living in dual-career families, to gain further insight into the difficulties of balancing personal and professional responsibilities. Keywords: Dual-career household, Working moms, Division of labor